Highly sensitive fluorescent aptasensor for Salmonella paratyphi A via DNase I-mediated cyclic signal amplification. Issue 24 (19th November 2015) - Yan, Xing; Li, Wenkai; Liu, Keyi; Deng, Le
Abstract : An elegant aptasensor was developed for dual fluorimetric determination of Salmonella paratyphi A through DNase I-assisted target recycling enlargement. Abstract : Outbreaks of Salmonella paratyphi A ( S. paratyphi A ) infection continue to occur worldwide and have drawn close attention. A useful practical detection platform is essential to the early rapid diagnosis of the infection. In this study, a simple and cost-effective DNA aptasensor was constructed, which was composed of a designed aptamer (DA) and two short carboxyfluorescein (FAM)-modified sequences (probe 1 and probe 2) for fluorimetric determination of S. paratyphi A . In the absence of a target, the two-FAM aptasensor (the aptasensor) was bound to graphene oxide (GO) and the fluorescence of FAM was quenched. In the presence of a target, however, the aptasensor was released from the surface of GO due to specific binding of the aptasensor to the target and a strong fluorescence signal could subsequently be detected. More importantly, the fluorescence signal could be substantially amplified by a DNase I-mediated target recycling process. Under the optimized conditions, the fluorescence intensity increased linearly with the target concentrations ranging from 1 × 10 2 to 1 × 10 11 cells per mL with a detection limit of 1 × 10 2 cells per mL. These results demonstrated that this detection platform exhibited high sensitivity and specificity for the detection of S. paratyphi A, and it might even be a potential alternative approach for the detection of other bacteria.